Identification of HCC-Related Genes Based on Differential Partial Correlation Network - Gao, Yuyao; Chang, Xiao; Xia, Jie; Sun, Shaoyan; Mu, Zengchao; Liu, Xiaoping (Frontiers in Genetics, 2021)
Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related death, but its pathogenesis is still unclear. Due to disease is involved in multiple biological processes, systematic identification of disease genes and module biomarkers can provide a better understanding of disease mechanisms. In this study, we provided a network-based approach to integrate multi-omics data and discover disease-related genes. We applied our method to HCC data from The Cancer Genome Atlas (TCGA) database, and obtained a functional module with 15 disease-related genes as network biomarkers. The results of classification and hierarchical clustering demonstrate that the identified functional module can effectively distinguish between the disease and the control group in both supervised and unsupervised methods. In brief, this computational method to identify potential disease functional module could be useful to disease diagnosis and further mechanism study of complex disease.